Preparing for the next generation pharmacists - Joseph T. DiPiro (Centro de Investigaciones y Publicaciones Farmaceuticas, 2020)
To address the changes in health care and the needs of society related to medicines, we must redefine the profession of pharmacy. We have defined the next generation pharmacists (NGP) as "a health care provider and change agent on the interprofessional health care team, personalizing medication use, managing safe and effective medication systems, and creating healthier communities." Schools and colleges of pharmacy should thoroughly examine their curriculum to ensure it is preparing pharmacists for this future. By creating a vision for the NGP and implementing the best curriculum, we ensure that pharmacists of the future will be up to the challenge of our society's health care needs.